Determination of the effects of oxygen-enriched air with the help of zeolites on the exhaust emission and performance of a diesel engine - Hazar, Hanbey; Tekdogan, Remziye; Sevinc, Huseyin (Pergamon-Elsevier Science Ltd, 2021)
The aim of the present experimental study is to reduce exhaust emissions and improve performance by feeding a diesel engine with oxygen enriched air by the help of natural and synthetic zeolites. Oxygen enrichment process is carried out by a zeolite filter (ZF) system that operates by the pressure swing adsorption (PSA) method. In the experiments, clinoptilolite-type natural zeolite (NZ) in 1.3-3 mm fractions and 0.4-0.8 mm 13X HP type synthetic zeolite (SZ) were used. Scanning electron microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDX) were used to observe the surface and particle structures of NZ and SZ and to perform the elemental analysis. According to the data obtained from the ZF system, NZ and SZ provided oxygen increases of 18.57% and 41.91%, respectively, when compared to the rate of oxygen in the air of the test environment. As a result of feeding the intake line of the engine with oxygen enriched air by using NZ and SZ, decreases in the carbon monoxide (CO), hydrocarbon (HC), smoke density, and brake specific fuel consumption (BSFC) values and increases in the nitrogen oxide (NOX), vibration, noise, exhaust gas temperature (EGT), and brake thermal efficiency (BTE) values were observed. (C) 2021 Published by Elsevier Ltd.
Keywords: Natural zeolite; Synthetic zeolite; Oxygen enrichment; Diesel engine; Exhaust emissions; Artificial neural network